Beyond Conventional Terms: Green Clauses and Digital Innovations in Uzbekistan's Commercial Contracts - Toqsanbaeva Ayjamal, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper explores the burgeoning field of green clauses in commercial contracts within the evolving legal landscape of Uzbekistan. Amidst global efforts to combat climate change and transition towards a green economy, integrating environmental responsibility into business operations through contractual mechanisms has become paramount. This study identifies a significant gap in Uzbekistan's current legal framework regarding the precise definition and systematic application of such clauses in commercial agreements. Utilizing a comprehensive legal analysis, the research aims to clarify the legal nature of green clauses, examine their practical implementation, and propose concrete recommendations for enhancing their efficacy. A central finding highlights how these clauses redefine contractual freedom by inherently incorporating ecological accountability. The study gains particular relevance from recent Uzbek legislative reforms, including the Law on Limiting Greenhouse Gas Emissions, which introduces pivotal concepts like "carbon units" and "carbon footprint" into national law, thereby laying a foundational legal basis for market-based environmental instruments. Furthermore, the paper briefly touches upon the new "green" public procurement initiatives, emphasizing their role in fostering environmentally responsible business practices. The ultimate goal is to contribute to a robust legal framework that supports sustainable development and aligns Uzbekistan's commercial sector with international green standards.